2023
DOI: 10.1007/s00704-023-04514-0
|View full text |Cite
|
Sign up to set email alerts
|

Indian summer monsoon simulations in successive generations of the NCAR Community Atmosphere Model

Abstract: Four generations of the NCAR Community Atmosphere Model 4, 5, and 6) are evaluated for the Indian summer monsoon (ISM) simulations. Total precipitation simulated by successive versions of CAM is overestimated over the western equatorial Indian Ocean (EIO), Arabian Sea, and Western Ghats (WGs), and underestimated over the eastern EIO, Bay of Bengal (BoB), and Indo-Burmese mountains, due to overestimated convective and underestimated large-scale precipitation, respectively. Overestimation of total precipitatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…The model used here for numerical sensitivity experiments is the Community Atmospheric Model version 6.0 (hereafter CAM6) as the atmospheric component of the National Center for the Atmospheric Research (NCAR) Community Earth System Model (CESM) version 2.1 (Danabasoglu et al, 2020). Kumar et al (2021) have systematically compared the MJO simulation fidelity from CAM3 to CAM6 and found that the newest generation owns the highest skill in capturing the eastward propagation of MJO from Indian Ocean to the western Pacific. We run the CAM6 with a horizontal resolution of 1.9° × 2.5° and 34 pressure levels from the surface to the top of the atmosphere (3.6 hPa).…”
Section: Full Agcm Experimentsmentioning
confidence: 99%
“…The model used here for numerical sensitivity experiments is the Community Atmospheric Model version 6.0 (hereafter CAM6) as the atmospheric component of the National Center for the Atmospheric Research (NCAR) Community Earth System Model (CESM) version 2.1 (Danabasoglu et al, 2020). Kumar et al (2021) have systematically compared the MJO simulation fidelity from CAM3 to CAM6 and found that the newest generation owns the highest skill in capturing the eastward propagation of MJO from Indian Ocean to the western Pacific. We run the CAM6 with a horizontal resolution of 1.9° × 2.5° and 34 pressure levels from the surface to the top of the atmosphere (3.6 hPa).…”
Section: Full Agcm Experimentsmentioning
confidence: 99%